Thigh muscle strength predicts knee replacement risk independent of radiographic disease and pain in women – data from the Osteoarthritis Initiative - Culvenor, Adam (Arthritis Rheumatol, 2016)
OBJECTIVE: To determine whether thigh muscle strength predicts knee replacement (KR) risk, independent of radiographic severity and pain. METHODS: Osteoarthritis Initiative participants with KR at 12–60 month (M) follow-up (cases) were each matched with one control (no KR throughout 60M) by age, sex, height, body mass index, baseline radiographic stage, and location of joint space narrowing. Isometric knee extensor and flexor strength were recorded biennially. The strength examination prior to KR (≤2 years) was termed T(0), that two years prior to T(0) T(−2), and that four years prior T(−4). Muscle strength between cases and controls was compared using paired t-tests and conditional logistic regression adjusted for pain. RESULTS: 136 of 4796 participants (60% women, age 65±9 years, BMI 29±4 kg/m(2)) received a KR during follow-up, had at least T(0) strength data, and a matched control. Knee extensor strength at T(0) (primary outcome) was significantly lower in female cases than controls (p<0.001; pain-adjusted odds ratio [ORp] 1.72, 95% confidence interval [CI] 1.16 to 2.56), but no difference was seen in men (p=0.451; ORp 0.80, 95%CI 0.50 to 1.27). Results were similar for knee flexor strength at T(0), and for longitudinal change in extensor and flexor strength between T(0) and T(−2). Thigh muscle strength at T(−2) or T(−4), or change between T(−2) and T(−4), did not predict KR risk in men or women. CONCLUSION: Thigh muscle strength predicted KR risk in women, but not in men. These results may identify a window for modifying risk of KR surgery in women.